Ambivalent Outcomes of Cell Apoptosis: A Barrier or Blessing in Malaria Progression - Kakani, Parik; Suman, Sneha; Gupta, Lalita; Kumar, Sanjeev (Frontiers in Microbiology, 2016)
The life cycle of Plasmodium in two evolutionary distant hosts, mosquito, and human, is a complex process. It is regulated at various stages of developments by a number of diverged mechanisms that ultimately determine the outcome of the disease. During the development processes, Plasmodium invades a variety of cells in two hosts. The invaded cells tend to undergo apoptosis and are subsequently removed from the system. This process also eliminates numerous parasites along with these apoptotic cells as a part of innate defense against the invaders. Plasmodium should escape the invaded cell before it undergoes apoptosis or it should manipulate host cell apoptosis for its survival. Interestingly, both these phenomena are evident in Plasmodium at different stages of development. In addition, the parasite also exhibits altruistic behavior and triggers its own killing for the selection of the best ‘fit’ progeny, removal of the ‘unfit’ parasites to conserve the nutrients and to support the host survival. Thus, the outcomes of cell apoptosis are ambivalent, favorable as well as unfavorable during malaria progression. Here we discuss that the manipulation of host cell apoptosis might be helpful in the regulation of Plasmodium development and will open new frontiers in the field of malaria research.